Non-fatal injury in Thailand from 2005 to 2013: Incidence trends and links to alcohol consumption patterns in the Thai Cohort Study - Wakabayashi, M.; Berecki-Gisolf, J.; Banwell, C.; Kelly, M.; Yiengprugsawan, V.; McKetin, Rebecca; Seubsman, S.; Iso, H.; Sleigh, A.; Chokhanapitak, J.; Khamman, S.; Pangsap, S.; et al. (Japan Epidemiological Association, 2016)
Background: We analyzed population-based injury trends and the association between injury and alcohol consumption patterns in Thailand, a middle-income country undergoing rapid social change. Methods: A nationwide cohort of 42 785 Thai adult Open University students, who were aged 15 to 87 years at enrolment, participated in cross-sectional assessments at baseline (2005) and 8 years later (2013). Incident non-fatal traffic and non-traffic injuries were recorded. Alcohol consumption patterns were categorized as follows: nondrinkers, occasional light drinkers, occasional heavy drinkers, regular drinkers, and ex-drinkers. Logistic regression was used to assess associations in 2005 and 2013 between injuries and alcohol consumption. We adjusted odds ratios (ORs) for socio-demographic factors, stress, health behaviors, and risk-taking behaviors. Results: Incidence estimates in 2013 were standardized to the age structure of 2005: the standardized rates were 10% (95% confidence interval [CI], 9.32-9.89) for participants with at least one non-traffic injury and 5% (95% CI, 4.86-5.29) for those with at least one traffic injury. Both standardized incidences for non-traffic and traffic injuries were significantly lower than corresponding rates in 2005 (20% and 6%, respectively). Alcohol consumption was significantly associated with non-traffic injury in 2005, but the association disappeared in 2013. For example, nontraffic injury was associated with regular drinking (adjusted OR 1.17; 95% CI, 1.01-1.40) in 2005, but not in 2013 (adjusted OR 0.89; 95% CI, 0.73-1.10). In both survey years, traffic injury was not associated with occasional heavy drinking when adjusted for health and risk-taking behavior. Conclusions: We examined non-fatal injury and the health-risk transition in Thailand in 2005 and 2013. Our data revealed decreases in alcohol consumption and non-fatal injury in the Thai Cohort between 2005 and 2013. Alcoholrelated injury in Thailand today could be amenable to preventive intervention.